2009
DOI: 10.1016/j.jbankfin.2008.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of domestic and cross-border bank acquisitions in the European Union

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
81
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 24 publications
10
81
0
10
Order By: Relevance
“…Several papers investigate the characteristics of merged firms from the former perspective (Hasbrouck, 1985;Morck et al, 1989;Martin and McConnell, 1991;Hernando et al, 2009). Numerous studies in this field find evidence of the disciplinary role of mergers that are often called hostile takeovers 5 .…”
Section: Determinants Of Mergersmentioning
confidence: 99%
“…Several papers investigate the characteristics of merged firms from the former perspective (Hasbrouck, 1985;Morck et al, 1989;Martin and McConnell, 1991;Hernando et al, 2009). Numerous studies in this field find evidence of the disciplinary role of mergers that are often called hostile takeovers 5 .…”
Section: Determinants Of Mergersmentioning
confidence: 99%
“…10 A large related literature examines the determinants of cross-border banking, which is usually accomplished via acquisition. Generally, these studies have found that large efficient banks (from developed financial systems) are more likely to be engaged in overseas expansion (Berger et al 2000;Pozzolo 2001a, 2001b;Buch and DeLong 2004;Berger 2007;Havrylchyk and Jurzyk 2007;Buch and DeLong 2003;Hernando et al 2009;Correa 2009). The reasons for bank and insurance firm expansion within Europe appear to be similar (Pozzolo and Focarelli 2007).…”
Section: Geographic Diversificationmentioning
confidence: 99%
“…That is, it is a model used to predict the probabilities of the different possible outcomes of a categorically distributed dependent variable, given a set of independent variables. This method is particularly an appropriate method for entry mode analysis when (i) the dependent variable outcome is multinomial distributed, (ii) underlying assumptions of multivariate normality are not met, (iii) dependent variable that can fall into one of several ordered or unordered categories (see the studies of Hernando, Nieto, & Wall, 2009;Sanfilippo Azofra, Garcia Olalla, & Torre Olmo, 2008;Wei, Liu, & Liu, 2005;Worthington, 2004). As noted earlier, there are five possible discrete outcomes of entry mode choices.…”
Section: Methodsmentioning
confidence: 99%